Analyzing the surface layer after WEDM depending on the parameters of a machine for the 16MnCr5 steel. (December 2016) - Mouralova, K.; Matousek, R.; Kovar, J.; Mach, J.; Klakurkova, L.; Bednar, J.
Abstract: The efficient wire electric discharge machining (WEDM) technology is a trade-off between the cutting speed and the resulting surface quality. A typical morphology of a surface machined using WEDM contains a large number of craters caused by the electric sparks generated in the cutting process. The paper analyzes the influence of the cutting speed on the quantitative and qualitative evaluation of the craters formed on the surface of a workpiece made of the 16MnCr5 steel. Applying metallography to cross-section microscopic slides, diffusion subsurface damages were studied caused by the cutting. The diffusion processes taking place between the electrode and the material machined were studied using a local point EDX microanalysis applied both to the machined surfaces and to the cross sections. A detailed study was also carried out of the brass electrode to measure its wear rate caused by the cutting process as well as its degradation in terms of the quality of its morphology and the chemical composition of surface.